Evaluation of stability of three different mini-implants, based on thread shape factor and numerical analysis of stress around mini-implants with different insertion angle, with relation to en-masse retraction force - Safiya Sana; Rekha Reddy; Ashok Kumar Talapaneni; Arshad Hussain; Sayeeda Laegue Bangi; Asma Fatima (Dental Press Editora, 2021)
ABSTRACT Objectives: Assess the stability of three different mini-implants, based on thread shape factor (TSF), and evaluate stresses at the mini-implant site and surrounding cortical bone on application of retraction force, at two different insertion angles. Methods: Mini-implants of three different diameters (M1 - Orthoimplant, 1.8mm), (M2 - Tomas, 1.6mm) and (M3 - Vector TAS, 1.4mm) and length of 8mm were used. Using scanning electronic microscopy, the mean thread depth, pitch and relationship between the two (TSF) were calculated. The mini-implants were loaded into a synthetic bone block and the pull-out strength was tested. One way ANOVA and Tukey post-hoc tests were used to compare the pull-out strength of mini-implants. P values < 0.05 were considered statistically significant. Finite element models (FEM) were constructed with insertion angulation at 90° and 60°, with retraction force of 150 g. The results were analyzed using ANSYS software. Results: Statistically significant difference was found among all the three mini-implants for thread depth and pitch (< 0.001). Statistically significant higher pull-out force value was seen for Orthoimplant. The stress distribution level in mini-implant and surrounding bone was observed to be smaller for Orthoimplant. Conclusion: Orthoimplant mini-implants have more favorable geometric characteristics among the three types, and less stress with 90°angulation.